The dynamics of Pueblo de Panay Township in Roxas City marketing and brand equity effects - Barredo, Rowela A.
This research paper explores the dynamics between Pueblo de Panay (PdP's) current marketing practices and its brand equity in Roxas City.While experienced in marketing real estate development for residential subdivisions, PdP is a newbie in marketing township developments. In formulating marketing strategies for this 400-hectare township, themarketing team needs data and information derived from surveys and interviews in the locality in order to come up with action plans and strategies that work. The researchers interviewed PdP's marketing team, and conducted a survey online for Facebook users in Roxas City in order to get necessary data that helped measure its current brand equity, including brand awareness, brand association, and brand loyalty.Results show that local consumers display a great sense of awareness of a positive association to, and a good measure of loyalty to the PdP brand, a sign that both traditional and digital marketing practices are working. Asimilar survey is recommendable to be conducted after a couple of years using a larger sample of respondents and in both online and offline platforms.